Poor Puppy and Bad Kitty - Bruel, Nick (Bruel, Nick. Bad Kitty., 2012)
When Bad Kitty won't play with him, Poor Puppy has to amuse himself with an alphabetical list of toys and dreams of playing in an alphabetical list of countries.